2022
DOI: 10.3389/fnagi.2022.838214
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Cognitive Reserve in Cochlear Implant Recipients

Abstract: At present, dementia is a hot topic. Hearing loss is considered to be a modifiable risk factor for cognitive decline. The underlying mechanism remains unclear and might be mediated by socioeconomic and psychosocial factors. Cochlear implantation has been shown not only to restore auditory abilities, but also to decrease mental distress and to improve cognitive functions in people with severe hearing impairment. However, the promising results need to be confirmed. In a prospective single-center study, we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 101 publications
(136 reference statements)
2
33
0
4
Order By: Relevance
“…Therefore, cochlear implantation might have a booster effect on cognition which might decline in the follow-up. Data by our group as well as in the literature did not show a correlation between speech perception and cognition or between the improvement in speech perception and in cognitive performance (32,44,85). Thus, it is not clear whether this enhancement is really direct due to an improvement in auditory abilities or whether it is indirect due to a general stimulating effect.…”
Section: Long-term E Ects Of Cochlear Implantation and Comparisonmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, cochlear implantation might have a booster effect on cognition which might decline in the follow-up. Data by our group as well as in the literature did not show a correlation between speech perception and cognition or between the improvement in speech perception and in cognitive performance (32,44,85). Thus, it is not clear whether this enhancement is really direct due to an improvement in auditory abilities or whether it is indirect due to a general stimulating effect.…”
Section: Long-term E Ects Of Cochlear Implantation and Comparisonmentioning
confidence: 52%
“…Furthermore, in most studies mean cognitive changes were evaluated for the whole study group, but not on an individual level. Only a few have analyzed the performance of individuals themselves ( 23 , 28 , 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…Together with the cited literature, we conclude that CI treatment improves speech perception and HRQOL of elderly CI recipients. Benefits, however, are also evident outside the audiometric booth: CI treatment can be one key element for delaying dementia progression or even regaining cognitive capabilities [ 30 , 49 ]. Accordingly, Wick et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that CI use has benefits beyond increased hearing abilities [ 16 , 17 , 18 ]. CI treatment in elderly people reduces tinnitus; depression; and somatization disorders; and, importantly in the context of elderly CI recipients, decreases loneliness, arrests cognitive decline and even increases cognitive functions, and increases HRQOL [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation